PENGAWETAN TIGA JENIS BAMBU DENGAN METODE RENDAMAN DINGIN - Barly Barly; Pipin Permadi (Jurnal Penelitian Hasil Hutan, 1987)
Cold soaking tests of three bamboo species in Formula 7 preservative  were performed.  Results indicated that cold soaking  in one day with 5%  Formula 7 gives satisfactory  penetration  and retention in the specimens of betung and andong species. The specimens of  tali species gave satisfactory  results when treated in three days.